Pengujian Getaran Dengan Eksitasi Kejut Dan Random Pada Komponen Struktur Dengan Profil Pelat Aluminium - Rizky Arman; Yovial Mahyoedin; Wenny Marthiana; Duskiardi Duskiardi (JURNAL KAJIAN TEKNIK MESIN, 2020)
Experimental vibration analysis to determine the dynamic behavior of the vibration system is observed from the response of the system to the stimulus acting on it. In this case the relationship between the stimulus at a certain location and direction is specifically related to the response at a certain location and direction. The relationship between stimulus and response is called the Frequency Response Function (FRF) or better known as the transfer function. In measuring the transfer function, the stimulus to the structure is given in the form of excitation force while the vibration response measurement depends on the type of sensor (transducer) used. Departing from the above problems, vibration testing is carried out on a structural model. This test uses an Aluminum beam as a specimen by using an excitation signal from the exciter and impact hammer. The response signal comes from the accelerometer, while the excitation force signal comes from two different type transducers.